Bioinspired enamel repair via inorganic ionic polymerization using calcium phosphate ionic clusters and nano-hydroxyapatite - Marwa A. Elkhouly; Mahmoud M. Emara; Norhan Nady; Ahmed S. Elkadi; Sherif H. Kandil (Scientific Reports)
Abstract Traditional restorative materials often fail to integrate seamlessly with natural tooth structures due to differences in chemical composition, leading to microleakage and related clinical problems. This study aims to create a material entirely composed of calcium phosphates, the main component of dental enamel, to repair minor enamel cavities. Inspired by the biomineralization process and employing the inorganic ionic polymerization strategy, a cohesive calcium phosphate mass was developed to repair minor enamel cavities. Calcium phosphate ionic clusters (CPICs) and three types of calcium phosphate powder were utilized; (bone-derived and synthetic hydroxyapatite; (BHA and SHA), and dried CPICs. Two different techniques, namely layer by layer (LbL) and premixing (PM), were employed to mix CPICs with one type of calcium phosphate powder to form a cohesive mass. Different analysis techniques were used including FTIR, XRD, SEM and TEM. Among the tested approaches, the mass formed by mixing BHA with CPICs using the PM technique demonstrated superior integration with enamel walls and infiltration of calcium phosphate particles into enamel. To the best of our knowledge, repairing cavitated enamel defects using a bioinspired approach with a material composed entirely of calcium phosphate has not yet been achieved.